Unleashing the Potential of Learning Agility: A Catalyst for Innovative Work Behavior and Employee Performance - Wolor, Christian Wiradendi; Suhud, Usep; Nurkhin, Ahmad; Hoo, Wong Chee; Rababah, Mahmoud Ali (Public Health of Indonesia, 2025)
Background: In today’s rapidly evolving business environment, particularly in the information technology (IT) sector, learning agility has emerged as one of the most crucial competencies for workforce adaptability, ranking as the second most sought-after skill in recruitment after advanced cognitive abilities. Companies in this industry require employees who can quickly adapt to new software, programming languages, and emerging technologies, yet many fresh graduates struggle with learning agility assessments, resulting in lower employability rates in competitive firms. Objective: This study aims to fill the gap in previous research by empirically testing how learning agility influences employee performance through IWBs in IT companies, thereby providing a novel contribution to understanding the factors that support workforce innovation and competitiveness in this sector. Methods: This study used a quantitative methodology, which involved a structured survey instrument and structural equation modeling (SEM) for data analysis. The study was conducted between March and May 2024 with a sample size of 200 respondents from employees working in the information technology (IT) industry in Indonesia. Results: The findings reveal that learning agility significantly enhances IWB (p=0.000), which in turn positively influences employee performance (p=0.006). Conclusion: These results emphasize the need for companies to not only prioritize learning agility during recruitment but also to foster a work environment that supports continuous learning through structured training programs, cross-functional project opportunities, and mentorship initiatives, ensuring employees remain agile and innovative in response to technological advancements. Keywords: learning agility; innovative work behaviour; employee performance